2017
DOI: 10.25289/ml.2017.6.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Photobiomodulation on Wound Healing of the Corneal Epithelium through Rho-GTPase

Abstract: Background and ObjectivesIn recent years, photobiomodulation (PBM) using low-level light has been applied to diverse clinical approaches because of its potential to elevate the cell metabolism or regulate various signaling pathways. This study evaluated the possibility of a short term effect of PBM on the wound healing of corneal epithelial cells. Rapid healing of the corneal epithelium and the return of an intact basement membrane can restore the eye's normal mechanical barriers. The migration, proliferation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…38,23 This range of wavelengths is known as optical window, being overlapped with the absorption spectrum of cytochrome C oxidase. 23 Yet, a previous study confirmed the effect of 740 nm in wound healing, 26 implying the wavelengths in the optical window may as well be effective. Although LLLT with inadequate parameters may be ineffective and even cause unwanted inhibitory effects, 22 what is known regarding LLLT and its parameters is still at basic level, and more information should be needed to define accurate parameters.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…38,23 This range of wavelengths is known as optical window, being overlapped with the absorption spectrum of cytochrome C oxidase. 23 Yet, a previous study confirmed the effect of 740 nm in wound healing, 26 implying the wavelengths in the optical window may as well be effective. Although LLLT with inadequate parameters may be ineffective and even cause unwanted inhibitory effects, 22 what is known regarding LLLT and its parameters is still at basic level, and more information should be needed to define accurate parameters.…”
Section: Discussionmentioning
confidence: 83%
“…Also, the degree of des- quamation and the number of detached epithelial cells decreased after LLLT, showing the increased density and epithelial tissue stabilization. LLLT using NIR is known to increase the migration capacity of corneal epithelial cells in short time, 26 and enhance the wound healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that LLLT is effective in various fields, including treatment of alopecia, 16 vestibulopathy, 17 and ophthalmic diseases. 18,19 However, the mechanism of LLLT has not been fully elucidated. Current research has shown that the effects of LLLT involve the absorption of photons from the laser to cytochrome c oxidase in cells, leading to stimulation of the electron transport chain and promotion of ATP production.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, therapeutic agents that act on RhoA-GTPase in the intestine, or restore basal sodium-proton exchange in the enterocyte, could mitigate endotoxins' effects on the intestinal barrier function. Photobiomodulation proved to be effective in activating RhoA-GTPase, stimulating corneal epithelial cells (Hackam et al, 2005;Rhee et al, 2017).…”
Section: Discussionmentioning
confidence: 99%